Precision treatment paradigm: Genomic features and therapeutic implications in mesenchymal‐epithelial transition‐amplified gastric cancer - Yiyi Yu; Zhening Zhang; Mengxuan Zhu; Yu Shan; Yan Wang; Li Wei; Xuan Huang; Debin Sun; Zhao Peng; Tianshu Liu (Wiley, 2024)
Abstract Background Despite advances in treatments for gastric cancer (GC), new targets are needed to enhance treatment, especially when mesenchymal‐epithelial transition (MET) amplification is involved. Therefore, we investigated the genomic features of MET‐amplified GC and efficacy of anti‐MET therapy. Methods Genomic features were investigated in 2284 patients (cohort 1) and 438 patients in the Cancer Genome Atlas (TCGA cohort). RNA data were obtained from TCGA for expression analysis. Clinical responses of 71 patients (cohort 2) were investigated. Survival rates were compared by Kaplan-Meier and log‐rank tests. Results In cohort 1, 95 (4.2%) exhibited MET amplifications. In TCGA cohort, 15 (3.4%) exhibited MET amplifications. The five top mutated genes were TP53, CDH1, ARID1A, KMT2D and PIK3CA in cohort 1 and TTN, TP53, MUC16, LRP1B and SYNE1 in TCGA cohort. TP53, PIK3CA, KRAS and GNAS showed significant single nucleotide variants (SNVs) in cohort 1, and TP53 SNVs were significant in TCGA cohort. Fifteen and 18 genes showed significant copy number variations (CNVs) between the MET‐ and non‐MET‐amplified groups in cohort 1 and TCGA cohort, respectively. The PI3K pathway was significantly activated in Chinese patients with MET‐amplified GC (p = 0.002). TP53 expression is negatively associated with MET amplification. Real‐world data obtained with cohort 2 revealed that anti‐MET treatment significantly affected overall survival (OS) (p = 0.002), whereas CNVs did not affect progression‐free or OS even when treatment lines were considered. Conclusions MET‐amplified GC has a distinctive mutation landscape. Our findings provide valuable information for clinicians who treat patients with MET‐amplified GC.